الألفاظ العربية المقترضة في "قاموس الديوان" كتاب "بغية الطلاب" أنموذجا‏ ‏: دراسة وصفية تحليلية ‏\‏c‏ - Samirah bt Wazali (al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This study aims to investigate the neglect of loan-words (Arabic words in Malay language) in Kamus Ad-Diwan which studies on BughyatulTullab written by Sheikh Dawood Al-Fatani in Malay language (Jawi script). The objectives of this study, firstly is to highlight the biography and academic background of Sheikh Dawood Al- Fatani and the special features of BughyatulTullab from the point of knowledge and loan-words. Secondly, the definition of Kamus Ad-Diwan and its approach in selecting the loan-words, and the position in adopting the loan-words in Malay are also discussed. The researcher collected several loan-words from BughyatulTullab, and listed all the loan-words in Kamus Ad-Diwan. Finally, the researcher compared the two books to obtain the number of neglected loan-words in Kamus Ad-Diwan but still adopted in BughyatulTullab. At the end of this study, the researcher also managed to analyze and reveal some of the loan-words which experienced changes in terms of structure, semantics and method of writing when the loan-words are loaned into the Malay language (Jawi script).